Comparação entre eletrodos de tungstênio puro e dopados no processo de soldagem GTAW com CA onda retangular - Antunes, Juliano Okamoto (1999)
With the availability in the market of electronic power supplies, GTA welding with rectangular wave AC output has become possible. This feature overcomes problems (thermal efficiency and reversal polarity duration) due to the sine-shaped wave current output during Aluminum welding. This type of power supply improved remarkably welding of this material and its alloys, since an independent setting of current levels and durations is possible at each polarity. However, as the development of this type of power supply is recent, there is little information about this new version of the process. Therefore, the objective of this work was studying one of the parameters of rectangular AC GTAW, that is, the influence of some types of tungsten electrodes (pure, with Thorium oxides and with Lanthanum oxides) on electrode wear, under different current levels, negative duration times and tip angles. To carry out the experiments, a rig was set up in such a way that long time welds could be performed. A series of tests was carried out with different parameter combinations, each test taking 1,5 hours and with stops at every 10 minutes, to evaluate loss of mass and variation of tip electrode shape. The results indicated that electrodes with Lanthanum oxides exhibit lower wear rates and, consequently, longer life. Nevertheless, even using current levels recommended by handbooks and the electrode working mainly as the cathode, tip damage was observed. The Lanthanum electrode could have a balling tip instead of having its tip damaged if correct welding parameters are used. Similar behavior, but with higher wear rate, shorter life and no tip balling, was observed with Thorium electrodes. Pure Tungsten electrode, despite its larger wear rates, presented no tip damage with its tip becoming balled, independently of the welding parameters. The results also permitted to elaborate a model to explain the influence of current level and tneg/tpos ratio on pure electrode tip balling. The existing models to explain wear mechanisms of doped electrodes were criticized, since those do not consider temperature and emissivity iteration.